Human Melanoma: Drug Resistance - Röckmann, Heike; Sinha-von Jaschke, Pranav; Schadendorf, Dirk (Chemosensitivity Testing in Oncology, 2003)
Advanced malignant melanoma has a poor prognosis since chemotherapy is mostly ineffective because, in part, of the intrinsic and/or extrinsic resistance of melanoma cells to systemic treatment with antineoplastic agents. The reasons for the chemoresistant phenotype are currently unknown. The relevance of well-analyzed drug resistance mechanisms in melanoma such as intracellular and extracellular transport, drug resistance by induction of certain enzyme systems, and altered drug-target interaction is reviewed. It has been shown that most anticancer drugs kill susceptible cells through induction of apoptosis. Therefore, the significance of apoptotic deficiency caused by alteration in the apoptotic pathway is discussed in relation to specific molecules and apoptotic mechanisms like death-receptors, the Bcl-2 family, and the Hsp family of proteins. The complexity of the molecular variants involved in signal transduction along apoptotic pathways suggests that the cell may possess a variety of possibilities for regulating apoptosis and generating apoptosis deficiency. Thus apoptosis and apoptosis deficiency should be analyzed to understand the mechanisms of melanoma resistance.